From Enron to Evo : Pipeline Politics, Global Environmentalism, and Indigenous Rights in Bolivia - Hindery, Derrick, 1972- (Book collections on Project MUSE., 2013)
Throughout the Americas, a boom in oil, gas, and mining development has pushed the extractive frontier deeper into Indigenous territories. Centering on a long-term study of Enron and Shell's Cuiabá pipeline, this book traces the struggles of Bolivia's Indigenous peoples for self-determination over their lives and territories. In his analysis of their response to this encroaching development, the author also sheds light on surprising similarities between neoliberal reform and the policies of the nation's first Indigenous president, Evo Morales.